Exciton dynamics and photoresponse behavior of the in situ annealed CsSnBr3 perovskite films synthesized by thermal evaporation. (20th August 2022) - Jia, Junlin; Wang, Ruibin; Mu, Haichuan
Abstract: The CsSnBr3 photodetectors are fabricated by thermal evaporation and 75 °C in situ annealing, and the effect of in situ annealing on the morphology, structure, exciton dynamics and photoresponse of thermally evaporated CsSnBr3 films are investigated. Especially, temperature dependent steady-state photoluminescence (PL) and transient PL decaying have been analyzed in details for understanding the exciton dynamics. Meanwhile, effect of annealing on the activation energy for trap sites ( E a ), exciton binding energy ( E b ), activation energy for interfacial trapped carriers (Δ E ), trap densities and carriers mobilities are studied and the annealed (A-CsSnBr3 ) reveals obviously lower E b and trap density together with notably higher carrier mobility than those of the unannealed (UA-CsSnBr3 ). Temperature dependence of the integrated PL intensity can be ascribed to the combining effect of the exciton dissociation, exciton quenching through trap sites and thermal activation of trapped carriers. The temperature dependent transient PL decaying analysis indicates that the PL decaying mechanism at low and high temperature is totally different from that in intermediate temperature range, in which combing effect of free exciton and localized state exciton decaying prevail. The beneficial effects of the in situ annealing on the photoresponse performance of the CsSnBr3 films can be demonstrated by the remarkable enhancement of the optimal responsivity ( R ) after in situ annealing which increases from less than 1 A W −1 to 1350 A W −1 as well as dramatically improved noise equivalent power, specific detectivity D * and Gain ( G ).